2011
DOI: 10.1002/pbc.23006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemotherapy on disseminated low‐grade glioma in children and adolescents: Report from the HIT‐LGG 1996 trial

Abstract: Complete MRI scan should be a standard diagnostic procedure in young children with hypothalamic-chiasmatic tumors especially if presenting with diencephalic syndrome. Dissemination in childhood LGG relates to impaired PFS. CT delays progression for responders. Multicenter studies have to evaluate the efficacy of extended treatment strategies in DLGG to improve outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 43 publications
10
56
0
Order By: Relevance
“…Primary dissemination of LGG has been described to be an unfavourable prognostic factor [32], [33], confirmed by this report with an impaired PFS. The impact of dissemination is statistically noticeable, suggesting that patients with disseminated tumours experience progression more frequently even following non-progression at response assessment at week 24.…”
Section: Discussionsupporting
confidence: 85%
“…Primary dissemination of LGG has been described to be an unfavourable prognostic factor [32], [33], confirmed by this report with an impaired PFS. The impact of dissemination is statistically noticeable, suggesting that patients with disseminated tumours experience progression more frequently even following non-progression at response assessment at week 24.…”
Section: Discussionsupporting
confidence: 85%
“…They are typically seen to be slow-growing, well-circumscribed tumors, which do not invade surrounding tissues and virtually never progress to higher malignancy grades. Dissemination into the spinal canal at diagnosis has been reported, but this is a rare event occurring in only 2–3% of cases [5]. As such, they are classified as malignancy grade I by the World Health Organisation, and prognosis in terms of overall survival is very good: >90% of patients survive beyond 10 years, and the majority of these long-term survivors are cured of their tumor [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Sixty-one patients (5.2%) were found to have tumor dissemination, with 2.8% being present at diagnosis. 8 Other reviews have found similar frequencies of dissemination ranging from 4% to 10%. 9,10 Various infectious and inflammatory lesions, immunemediated demyelinating or vascular disorders, and therapyinduced complications can produce lesions that mimic CNS neoplasms.…”
Section: Discussionmentioning
confidence: 77%